(untitled) (Asian Journal of Social Science Studies, 2017)
The main purpose of this pilot study is to examine and quantitatively explore a small sample of data on the determinants of strategic orientations and access to finance towards SMEs performance of the Gem and Jewelry Industry in Thailand. The proposed model consists of four elements that are used as a determinant of SMEs performance. A personally administered questionnaire approach was employed to collecting data from firms located in the Jewelry Trade Center, one of the most important premises for trading diamonds, gems, and jewelry in Thailand. The validity and reliability of the instruments were evaluated through panel of experts and data was analyzed using the SmartPLS 2.0.M3 software. The questionnaire revision was made based on the feedback of experts and the results confirmed that the remained items and constructs have good internal consistency reliability. A pilot test shows that there is no issue of validity and reliability of the instrument. The results of pilot test also will be beneficial to the further actual research on a larger scale by helping to avoid the potential research problems.